Genetic diversity of enterococci from Iranian home-made artisanal dairy products - Nejati, Fatemeh; Gatto, Veronica; Castioni, Anna; Tebaldi, Marta; Babaei, Mahdi; Fracchetti, Fabio; Felis, Giovanna E (Dairy science & technology, 2015)
Enterococci represent a significant part of microbiota in home-made dairy products due to their remarkable intrinsic resistance to critical growth conditions and technological properties. In this study, the predominant coccal lactic acid bacteria (LAB) were isolated from traditional dairy products made and largely consumed in villages of Chahar-Mahalo Bakhtiyari province of Iran. Thirty-six samples of home-made dairy products were collected from scattered households, and a total of 61 gram-positive and catalase-negative cocci were analyzed. Genetic fingerprinting (repetitive extragenic palindromic PCR (REP-PCR) and 16S–23S intergenic spacer (ITS) amplification) and gene sequencing (16S rRNA gene and pheS gene) were carried out to obtain an unambiguous identification of the isolates at the species level and to highlight genetic biodiversity among wild enterococci. It was shown that 42 out of 61 isolates belonged to Enterococcus spp., and Enterococcus faecium was the most frequently isolated species. Intraspecific diversity of the E. faecium species was further investigated, targeting the genes hyl, esp, and msrC, related to virulence and antibiotic resistance, and the results obtained suggest that two strains could be further characterized for possible use as starter cultures. In conclusion, the present study confirms that application of diverse independent molecular techniques is required to clearly identify Enterococcus spp. isolates and to unveil wild strain biodiversity. Moreover, a preliminary molecular screening of selected genetic features represents a fast and feasible approach to select, among a wide collection of isolates, the most promising candidates for further exhaustive characterization of safety and technological traits.